The endogenous peptide antisecretory factor promotes tonic GABAergic signaling in CA1 stratum radiatum interneurons - Strandberg, Joakim; Lindquist, Catarina; Lange, Stefan; Asztely, Fredrik; Hanse, Eric (Frontiers in Cellular Neuroscience, 2014)
Tonic GABAergic inhibition regulates neuronal excitability and has been implicated to be involved in both neurological and psychiatric diseases. We have previously shown that the endogenous peptide antisecretory factor (AF) decreases phasic GABAergic inhibition onto pyramidal CA1 neurons. In the present study, using whole-cell patch-clamp recordings, we investigated the mechanisms behind this disinhibition of CA1 pyramidal neurons by AF. We found that application of AF to acute rat hippocampal slices resulted in a reduction of the frequency, but not of the amplitude, of spontaneous IPSCs (sIPSCs) in CA1 pyramidal neurons. Miniature IPSCs (mIPSCs), recorded in the presence of tetrodotoxin (TTX), were however not affected by AF, neither in CA1 pyramidal cells, nor in stratum radiatum interneurons. Instead, AF caused an increase of the tonic GABAA current in stratum radiatum interneurons, leaving the tonic GABAergic transmission in CA1 pyramidal cells unaffected. These results show that the endogenous peptide AF enhances tonic, but not phasic, GABAergic signalling in CA1 stratum radiatum interneurons, without affecting tonic GABAergic signalling in CA1 pyramidal neurons. We suggest that this increased tonic GABAergic signalling in GABAergic interneurons could be a mechanism for the AF-mediated disinhibition of pyramidal neurons.